Using de novo genome assembly and high-throughput sequencing to characterize the MHC region in a non-model bird, the Eurasian coot - Pikus, Ewa; Minias, Piotr (Scientific reports, 2022)
Genes of the Major Histocompatibility Complex (MHC) form a key component of vertebrate adaptive immunity, as they code for molecules which bind antigens of intra- and extracellular pathogens (MHC class I and II, respectively) and present them to T cell receptors. In general, MHC genes are hyper-polymorphic and high MHC diversity is often maintained within natural populations (via balancing selection) and within individuals (via gene duplications). Because of its complex architecture with tandems of duplicated genes, characterization of MHC region in non-model vertebrate species still poses a major challenge. Here, we combined de novo genome assembly and high-throughput sequencing to characterize MHC polymorphism in a rallid bird species, the Eurasian coot Fulica atra . An analysis of genome assembly indicated high duplication rate at MHC-I, which was also supported by targeted sequencing of peptide-binding exons (at least five MHC-I loci genotyped). We found high allelic richness at both MHC-I and MHC-II, although signature of diversifying selection and recombination (gene conversion) was much stronger at MHC-II. Our results indicate that Eurasian coot retains extraordinary polymorphism at both MHC classes (when compared to other non-passerine bird species), although they may be subject to different evolutionary mechanism.